Osteoarthritis: epidemiology. - Arden, N; Nevitt, M (2006)
Osteoarthritis (OA) is the most common joint disorder in the world. In Western populations it is one of the most frequent causes of pain, loss of function and disability in adults. Radiographic evidence of OA occurs in the majority of people by 65 years of age and in about 80% of those aged over 75 years. In the US it is second only to ischaemic heart disease as a cause of work disability in men over 50 years of age, and accounts for more hospitalizations than rheumatoid arthritis (RA) each year. Despite this public health impact, OA remains an enigmatic condition to the epidemiologist. In this chapter, we will review the definition and classification of OA, its prevalence, incidence, risk factors and natural history.